FT-IR Technique in Marine Sludge Studies - K. Ponnarasi, G. Viruthagiri* and (Journal of Experimental Sciences, 2011)
FT-IR spectroscopy is a quick and useful method to monitor the sludge process: however any particular sludge mixture needs preliminary studies of the spectra. The FT-IR technique was used to distinguish between different types of organic contents and to derive information concerning their composition and structural changes upon chemical modification. No special accessories were used: the reported sampling technique is commonly available in the infrared laboratories. The selection of the sampling technique used depends on the purpose of the study and on the physical state of the sample. KBr pressed disk technique was found to be very useful for a routine characterization of sludge during heat treatment. The study then reviews the major scientific and technological advances, focusing principally on the developments in raw materials compositions resulting from the introduction of certain key raw materials to enhance composition quality. As the interpretations of unfired marine sludge compositions and the relation of fired marine sludge compositions have drawn particular attention from the scientific community, the paper addresses these issues in depth.Ã‚Â